The Democracy Development Machine Neoliberalism, Radical Pessimism, and Authoritarian Populism in Mayan Guatemala - Copeland, Nicholas (Cornell University Press, 2019)
Nicholas Copeland sheds new light on rural politics in Guatemala and across neoliberal and post-conflict settings in The Democracy Development Machine. This historical ethnography examines how governmentalized spaces of democracy and development fell short, enabling and disfiguring an ethnic Mayan resurgence. In a passionate and politically engaged book, Copeland argues that the transition to democracy in Guatemalan Mayan communities has led to a troubling paradox. He finds that while liberal democracy is celebrated in most of the world as the ideal, it can subvert political desires and channel them into illiberal spaces. As a result, Copeland explores alternative ways of imagining liberal democracy and economic and social amelioration in a traumatized and highly unequal society as it strives to transition from war and authoritarian rule to open elections and free-market democracy.The Democracy Development Machine follows Guatemala's transition, reflects on Mayan involvement in politics during and after the conflict, and provides novel ways to link democratic development with economic and political development. Thanks to generous funding from Virginia Tech and its participation in TOME (Toward an Open Monograph Ecosystem), the ebook editions of this book are available as Open Access (OA) volumes from Cornell Open (cornellpress.cornell.edu/cornell-open) and other Open Access repositories.